Isolated Hypoglossal Nerve Palsy: A Case Report - Bhandari, Anjali; Chandra, Avinash; Shrestha, Tejashwi; Rajbhandari, Reema (Annapurna Journal of Health Sciences, 2026)
The hypoglossal nerve; XII cranial nerve, exit the skull through the hypoglossal canal which is the primary motor nerve responsible for the innervation of the intrinsic and extrinsic tongue muscles Isolated hypoglossal nerve palsy is a rare clinical condition. It may have idiopathic cause and various secondary causes such as intracranial or extracranial space-occupying lesions, head and neck trauma, vascular abnormalities, infections, autoimmune disorders, or neuropathy. Here we present the case of an elderly male who attended the Outpatient Department with complaints of tongue deviation to the left side and slurred speech. This case underscores the importance of thorough investigation to ensure accurate diagnosis and optimal patient outcomes.